The effects of improved subsurface drainage on runoff and nitrogen leaching from a clayey field section - Jokinen, Vilma; Salo, Heidi; Mäkelä, Minna; Nurminen, Jyrki; Äijö, Helena; Laine‐Kaulio, Hanne; Myllys, Merja; Koivusalo, Harri (John Wiley & Sons, 2024)
The aim of this study was to investigate the effects of improved subsurfacedrainage installation on nitrogen (N) loss in drain discharge (DD) and topsoillayer runoff (TLR). Data on DD and TLR, as well as on concentrations of total,nitrate and ammonium N in the runoff components, were collected from foursections of an experimental field in southern Finland (June 2007–December2018). Supplementary drains were installed in one of the field sections in June2014, and the data from that section were compared with those from threereference sections. Differences between the sections were statistically analysedbased on annual and monthly values of runoff components and concentra-tions, as well as the loads of N fractions. The results revealed that improveddrainage increased the N load in the DD, reducing the load in the TLR.Changes in N loads were more clearly driven by changes in the runoff volumesrather than by changes in the N concentrations in the runoff waters. Before thedrainage improvement, most of the total N load was nitrate (53%), while theshare of rest N (fraction of the total N after the mineral N fractions were sub-tracted) was 45%. After improved drainage, the percentages of nitrate and restN were 73 and 26%, respectively. The results demonstrate the importance ofagricultural water management as the key driver for controlling nutrient loads.
Keywords: cumulative sums; long-term field experiment; N fractions; time series analysis